Cardio-metabolic abnormalities among patients with severe mental illness at a Regional Referral Hospital in southwestern Uganda. - David Collins Agaba; Richard Migisha; Godfrey Katamba; Scholastic Ashaba (PLoS ONE)
Patients with severe mental illness (SMI) have a higher burden of premature cardio-metabolic abnormalities, including diabetes mellitus, hypertension, hyperlipidemia, and obesity resulting into a 3-fold increase in mortality, and up to 20% reduction in life expectancy compared to the general population. Although over 30% of Ugandans have some form of mental illness, there are no national or hospital-based screening guidelines for cardio-metabolic abnormalities among these patients a general trend in most low-income countries. The screening rates for cardio-metabolic abnormalities in most low-income countries are at only 0.6%. The objective of this study was to describe the cardio-metabolic abnormalities among patients with SMI at Mbarara Regional Referral Hospital. Through a cross-sectional study, we recruited 304 patients with SMI and evaluated them for cardio-metabolic abnormalities using the National Cholesterol Education Programme Adult Treatment Panel III criteria for dyslipidemias, World Health Organisation criteria for diabetes mellitus, obesity, and the Joint national committee criteria for hypertension. We then determined the proportion of participants who met the criteria for each of the individual cardio-metabolic abnormalities. Of the 304 participants, 44.41% were male and 55.59% female with a mean age of 38.56±13.66 years. Almost half (46.38%) of the participants were either overweight or obese, 33.22% had abdominal obesity, 40.46% were hypertensive, 34.11% had low high-density lipoproteins, 37.42% had hypertriglyceridemia and 34.77% had hypercholesterolemia. Based on fasting blood sugar, 11.18% and 9.87% had pre-diabetes and diabetes respectively. There is a high level of cardio-metabolic abnormalities among patients with psychiatric disorders and thus metabolic screening for these abnormalities should be done routinely during psychiatric reviews. There is a need for national guidelines for screening of metabolic abnormalities among patients with SMI so that these abnormalities can be detected early enough at stages where they can be either reversed or delayed to progress to cardiovascular disease.